2017
DOI: 10.1111/1471-0528.14524
|View full text |Cite
|
Sign up to set email alerts
|

Cranberry capsules to prevent nosocomial urinary tract bacteriuria after pelvic surgery: a randomised controlled trial

Abstract: PAC prophylaxis does not reduce the risk of postoperative bacteriuria in patients undergoing pelvic surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 27 publications
1
15
1
Order By: Relevance
“…The fundamental outcome was after surgery, the urine bacterial count was estimated after 15 and 40 days. Pretreatment of cranberry proanthocyanidins did not decrease the occurrence of UTIs (Letouzey et al, 2017) .…”
Section: Urinary Tract Infection (Utis)mentioning
confidence: 81%
“…The fundamental outcome was after surgery, the urine bacterial count was estimated after 15 and 40 days. Pretreatment of cranberry proanthocyanidins did not decrease the occurrence of UTIs (Letouzey et al, 2017) .…”
Section: Urinary Tract Infection (Utis)mentioning
confidence: 81%
“…We appreciate the comment from Henry Botto and Amy B. Howell on our article ‘Cranberry Capsules to Prevent Nosocomial Urinary Tract Bacteriuria after Pelvic Surgery’ . They expressed concerns that the study was underpowered.…”
Section: Disclosure Of Interestsmentioning
confidence: 99%
“…We appreciate the comment from Henry Botto and Amy B. Howell 1 on our article 'Cranberry Capsules to Prevent Nosocomial Urinary Tract Bacteriuria after Pelvic Surgery'. 2 They expressed concerns that the study was underpowered. As we acknowledged in the article, the required patient number was not reached at the primary study endpoint; however, as a trend for lower rates for bacteriuria was observed for the placebo group in our cohort, the results would not be expected to reverse with a larger sample size.…”
Section: Sirmentioning
confidence: 99%
See 1 more Smart Citation
“…The recent study by Letouzey et al 1 in BJOG concluded that administering cranberry containing 36 mg of proanthocyanidin postoperatively does not reduce the risk of postoperative bacteriuria in patients receiving short-term transurethral catheterisation after pelvic surgery. However, significant methodological issues with the study confound this conclusion.…”
Section: Sirmentioning
confidence: 99%